Evaluation of Irrigation Network Performance Using the Irrigation System Performance Index (IKSI) Method in the Rejoso Irrigation Area: A Case Study of the Rejoso Kiri and Jati Secondary Canals - Ningrum, Fitriyanti Cahya; Saves, Faradlillah (Asosiasi Dosen Muda Indonesia, 2026)
Irrigation networks are essential infrastructures for supporting agricultural productivity, water distribution equity, and sustainable agricultural management. However, irrigation system performance is often affected by physical deterioration, limited operation and maintenance support, weak documentation, and institutional constraints. Objective: This study aims to evaluate the performance of the irrigation network in the Rejoso Irrigation Area, focusing on the Rejoso Kiri and Jati Secondary Canals, using the Irrigation System Performance Index (IKSI) method. Methodology: This research employed a descriptive quantitative approach through field surveys, direct observations, structured questionnaires, and secondary data collection from relevant agencies. Data were analyzed using the IKSI weighted scoring system, which assesses six main components: physical infrastructure, crop productivity, supporting facilities, organization and personnel, documentation, and the institutional condition of Water Users Associations (P3A). Findings: The results show that the overall IKSI value of the Rejoso Irrigation Area is 64.3%, which falls into the poor performance category and requires attention. The most critical aspects are related to physical infrastructure, supporting facilities, documentation, and P3A institutional performance. Implications: These findings imply that irrigation management improvement should not only focus on canal rehabilitation, but also on strengthening operation and maintenance facilities, improving documentation systems, and increasing P3A participation. Originality: The originality of this study lies in its location-specific evaluation of secondary canals by integrating technical, operational, and institutional aspects to provide targeted recommendations for improving irrigation system performance.